Mortalite A La Phase Aiguë De L’avc Hemorragique Sous Notre Protocole De Baisse De La Tension Arterielle A l’Hopital Universitaire (HU) Befelatanana Antananarivo - Andriamasinavalona, Rajaonarison Lala; Finiavana, Rasaholiarison Nomena; Santatra, Razafindrasata Ratsitohara; Julien, Razafimahefa; Noël, Zodaly; Djacoba, Tehindrazanarivelo Alain (European Scientific Journal, ESJ, 2018)
Introduction: Hemorrhagic stroke can be seen in 90% of cases with high blood pressure. It is a predictor of intra-hospital mortality. Our goal is to compare the mortality rate based on admission under our therapeutic strategy for HTA in the acute phase of stroke. Method: A retrospective descriptive, cross-sectional study of consecutive patients was conducted over a 12-month period during the year 2017. Results: We had 20% (3/15) mortality rate in acute phase in those with systolic blood pressure (SBP) in admission at ≥ 180 mmHg (group II) and no death (0/17) was recorded in the those with SBP in admission at 140-179mmHg (group I). A SBP at the 7th day (D7) less than 140 mmHg was not rich in those two groups: 35.29 % in group I (n=6) and 46.66 % in group II (n=7) respectively. The sex ratio was 1. High blood pressure remains the main cardio-vascular risk factor reported in our study (81.21%). All our patients had Glasgow scale value between 13-15 and only the NIHSS value > 10 was associated with high blood pressure in acute phase (p=0.0131). Brain CT Scan was realised in majority of cases at the second day (D2) of stroke (n=16). This, however, is with localisation preference in the basal ganglia, with intra-cerebral hemmorhage (ICH) scale at 1 in 65.62% (n=21) of cases. Conclusion: Intra-hospital mortality in acute phase of hemorrhagic stroke remains high. Instauration of stroke field in Madagascar is necessary and this gives the Befelatanana University Hospital a Neuro- Vascular Intensive Care Unit too.